FLNC Expression Level Influences the Activity of TEAD-YAP/TAZ Signaling - Knyazeva, Anastasia (Genes (Basel), 2020)
Filamin C (FLNC), being one of the major actin-binding proteins, is involved in the maintenance of key muscle cell functions. Inherited skeletal muscle and cardiac disorders linked to genetic variants in FLNC have attracted attention because of their high clinical importance and possibility of genotype-phenotype correlations. To further expand on the role of FLNC in muscle cells, we focused on detailed alterations of muscle cell properties developed after the loss of FLNC. Using the CRISPR/Cas9 method we generated a C2C12 murine myoblast cell line with stably suppressed Flnc expression. FLNC-deficient myoblasts have a significantly higher proliferation rate combined with an impaired cell migration capacity. The suppression of Flnc expression leads to inability to complete myogenic differentiation, diminished expression of Myh1 and Myh4, alteration of transcriptional dynamics of myogenic factors, such as Mymk and Myog, and deregulation of Hippo signaling pathway. Specifically, we identified elevated basal levels of Hippo activity in myoblasts with loss of FLNC, and ineffective reduction of Hippo signaling activity during myogenic differentiation. The latter was restored by Flnc overexpression. In summary, we confirmed the role of FLNC in muscle cell proliferation, migration and differentiation, and demonstrated for the first time the direct link between Flnc expression and activity of TEAD-YAP\TAZ signaling. These findings support a role of FLNC in regulation of essential muscle processes relying on mechanical as well as signaling mechanisms.